2007
DOI: 10.5897/ajb2007.000-2418
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocin and cellulose production by lactic acid bacteria isolated from West African soft cheese

Abstract: Sixteen colonies of lactic acid bacteria (LAB) were selected and screened for their ability to produce bacteriocin by agar well diffusion method using the supernatant of centrifuged test cultures. Four isolates inhibited the growth of Listeria monocytogenes and Escherichia coli. Lactobacillus plantarum (6) and Lactobacillus brevis (5) were the most dominant species. The remaining were Lactobacillus lactis (2), Streptococcus lactis (2) and Lactobacillus fermentum (1). Lactobacillus spp. accounted for 87.5% of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Furthermore, L. pentosus MP-10 also had genes coding for cellulose synthase (two genes exclusive to L. pentosus MP-10 and two other genes) involved in cellulose synthesis ( Table 3 ), which could accumulate cellulose on the cell wall surface as an extracellular matrix for cell adhesion and biofilm formation to protect the bacteria. Cellulose production has been reported in lactic acid bacteria ( Adetunji and Adegoke, 2007 ); however, no reports were found of cellulase production, although some Lactobacillus sp. genomes exhibit cellulase genes such as L. delbrueckii subsp.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, L. pentosus MP-10 also had genes coding for cellulose synthase (two genes exclusive to L. pentosus MP-10 and two other genes) involved in cellulose synthesis ( Table 3 ), which could accumulate cellulose on the cell wall surface as an extracellular matrix for cell adhesion and biofilm formation to protect the bacteria. Cellulose production has been reported in lactic acid bacteria ( Adetunji and Adegoke, 2007 ); however, no reports were found of cellulase production, although some Lactobacillus sp. genomes exhibit cellulase genes such as L. delbrueckii subsp.…”
Section: Resultsmentioning
confidence: 99%
“…Ingestion with the bacterial powder preparation of L. plantarum or cheese containing L. plantarum (10.0 log CFU per day for 3 weeks) was found to be safe [52]. Recently, L. plantarum strains have been isolated in a wide variety of traditional cheese products, such as different Italian and Iranian cheese varieties [9], Greek Melichloro cheese [42], Polish golka cheese [51], Serbian Zlatar cheese [56], Turkish Karin Kaymak cheese [55], Tibetan Qula cheese [17], Indian camel cheese [40], Brazilian ovine cheese [38], and West African soft cheese [4].…”
Section: Introductionmentioning
confidence: 99%
“…Twelve of them were bacteriocinproducing isolates of which two isolates were identified as L. lactis subsp lactis and Enterococcus faecium. In Nigeria, Adetunji and Adegoke (2007) identified L. plantarum and Lactobacillus brevis as the most dominant bacteriocin-producing LAB strains isolated from West African soft cheese however Lactococcus lactis, streptococcus lactis and Lactobacillus fermentum were less dominant. In France, Ennahar et al (1996) identified six bacteriocin-producing LAB isolates from cheese including three Lactococcus strains, two Enterococcus strains and one Lactobacillus strain which was active against Listeria organism.…”
Section: Discussionmentioning
confidence: 99%